Vocational vs. General Education and Employment over the Life-Cycle: New Evidence from PIAAC - Franziska Hampf; Ludger Woessmann (Center for Economic Studies and ifo Institute (CESifo), 2016)
It has been argued that vocational education facilitates the school-to-work transition but reduces later adaptability to changing environments. Using the recent international PIAAC data, we confirm such a trade-off over the life-cycle in a difference-in-differences model that compares employment rates across education type and age. An initial employment advantage of individuals with vocational compared to general education turns into a disadvantage later in life. Results are strongest in apprenticeship countries that provide the highest intensity of industry-based vocational education.
Keywords: J24; J64; I20; 330; vocational education; apprenticeship; employment; life-cycle; PIAAC